EXPLORING THE ROLE OF DIGITAL COMMUNICATION STRATEGIES IN ENHANCING CUSTOMER VALUE WITHIN B2B MARKETS - Sihem Guidoum; Lamia Ameur; Elkhansa Saadi (International Journal of Innovative Technologies in Social Science, 2025)
This study explores the impact of digital communication strategies on customer value within the B2B oil and gas services sector, focusing on email marketing, websites, social media, and search engines. A descriptive-analytical research design was used, with data collected from 42 clients of Lorus Company through a structured questionnaire. The data were analyzed using SPSS (Version 26), employing Pearson correlation, ANOVA, and multiple regression analysis to examine the relationships between digital communication strategies and customer value. The results indicate that email marketing has a significant positive effect on customer value, while websites, social media, and search engines show weak or statistically insignificant impacts. The study recommends that companies prioritize personalized email marketing to enhance customer engagement and value, while also refining website and search engine strategies to improve their effectiveness in B2B contexts.